Assessment of decontamination processes for dioxins and dioxin‐like PCBs in fish oil by physical filtration with activated carbon. (20th December 2017) - ,; Knutsen, Helle Katrine; Alexander, Jan; Barregård, Lars; Bignami, Margherita; Brüschweiler, Beat; Ceccatelli, Sandra; Cottrill, Bruce; Dinovi, Michael; Edler, Lutz; Grasl‐Kraupp, Bettina; Hoogenboom, Laurentius (Ron); et al.
Abstract: Following a request from the European Commission, the EFSA Panel on Contaminants in the Food Chain (CONTAM) provided a scientific opinion on the assessment of decontamination processes involving the adsorption with activated carbon and physical filtration of fish oil in order to reduce the amount of dioxins (polychlorinated dibenzo‐ p ‐dioxins (PCDDs) and polychlorinated dibenzofurans (PCDFs)) and dioxin‐like polychlorinated biphenyls (DL‐PCBs). All feed decontamination processes must comply with the acceptability criteria specified in the Commission Regulation (EU) 2015/786. Two feed business operators provided data on their respective decontamination processes, which were assessed in terms of the efficacy of the process and the absence of adverse effects in the nature and characteristics of the product after decontamination. The processes proved to be able to remove PCDD/Fs (82–95%) and DL‐PCBs (26–45%) from the fish oil, depending on the process used by the business operator. Given that the level of contamination is within the range of the tested untreated fish oil, it is possible to meet EU requirements for these contaminants after decontamination. The CONTAM Panel considered both the evidence provided by one of the business operators and information in the available literature to conclude that the proposed processes do not lead to any detrimental changes in the nature of the fish oil. However, the process can deplete some beneficial constituents (e.g. vitamins). Information was provided to demonstrate the safe disposal of the waste material. The CONTAM Panel concluded that, on the basis of the information submitted by the feed business operators, the proposed decontamination processes to remove dioxins (PCDD/Fs) and DL‐PCBs from the fish oil by means of activated carbon and physical filtration were compliant with the acceptability criteria provided for in Commission Regulation (EU) 2015/786 of 19 May 2015.